Comparison of Constraints to Poultry Producers in Delta State Nigeria - Ovwigho, Bishop O.; Mmereole, F.U.C.; Udeh, I.; Akporhuarho, P.O. (International Journal of Poultry Science, 2009)
The study was an inter-disciplinary one designed to investigate the constraints relevant to different poultry production systems. The sample size was 241 poultry farmers made up of extensive (210), semi-intensive (5) and intensive (26). A four-point rating scale was used to measure the constraints. Mean, Analysis of variance and correlation matrix were used in data analysis. The constraints faced by the extensive poultry farmers were inability to diagnose sick birds (M = 3.45), lack of market for eggs (M = 2.52), egg cracking (M = 2.98), lack of finance (M = 3.44) and loss of birds/eggs to thieves, predators and hazards (M = 3.17). The constraints faced by semi-intensive poultry producers were inability to diagnose sick birds (M = 4.00), lack of feeds (M = 3.00), transportation difficulties(M = 2.80), loss of birds and eggs to predators, thieves and hazards(M = 2.60), lack of finance(M = 3.80) and egg cracking (M = 3.40). The constraints to intensive poultry producers were mortality of adult bids (M = 2.85), diseases out-break (M = 2.58), lack of feeds (M = 2.88), transportation difficulties (M = 3.23), lack of finance (M = 2.65.), feather pecking/cannibalism (M = 3.00) and difficulties in sourcing for day-old chicks (M = 2.65). Lack of finance was a common constraint in the three systems of poultry production. There was a significant difference (p